Desain and Implementation of E-Commerce Websaite System in the Bakery Business in an Effort to Increase Sales and Marketing Using The Waterfall Method at The Prima Sari Bakery Facory - Emilia Murni; Dewi Diniati; Mustakim; Ismu Kusumanto; Anwardi (School of Industrial and System Engineering, Telkom University, 2020)
Prima Sari is a culinary industry in Pekanbaru which is engaged in bakery. Founded in 2003 and hasbranches outside the city. The problem faced is that the sale of Prima Sari Bakery is done manually. So far,the sales system is still relying on the media interaction with consumers using the invoice bookkeepingsystem, receipt. Prima Sari as a supplier of bakery products in the store experienced bookkeeping sales canbe calculated fully after a week of delivering bakery products to the store. The marketing coverage is notcomprehensive because it relies on the factory driver's pallets in delivering bread to outlets that contributeto the distribution of Prima Sari Bakery bakery products. The purpose of this research is to design a web ecommerce to increase sales and assist the process of overseeing sales activities in the bakery industry andexpanding the area of market share and media promotion through e-commerce web access. Using theWaterfall Method with black box tasting and user acceptance test (UAT) testing. The results of this studyare a website system that can be accessed by General Users to view products and information, UserMembers or Customers can access the Prima Sari Bakery product order process, Admin Users who canprocess website systems related to sales data, customer data and User Leaders which can access salesreport data at the Prima Sari Bakery factory